ПЕДАГОГИКАЛЫҚ ЖОҚАРЫ ОҚЫЎ ОРЫНЛАРЫ ТАЛАБАЛАРЫН КӘСИПЛИК ТАЯРЛАЎ ПРОЦЕССИНДЕ ДҮНЬЯҒА КӨРКЕМЛИК КӨЗҚАРАСТЫ РАЎАЖЛАНДЫРЫЎ - Уразимова, Т.В. (ILIM hám JÁMIYET, 2025)
The article is devoted to the issues of professional training in the field of fine and decorative and applied arts in pedagogical universities, as well as the process of artistic development of students in the learning process. In connection with the above, fine art is considered by us as one of the main means of educating a modern harmonious personality, a comprehensively developed person, educated, progressive, highly moral, possessing the ability to work, the desire to create and understanding the beauty of life.